Implementation of Electric Vehicle Policies in Reducing Carbon Emissions in the Special Capital Region of Jakarta - Meylinda, Anggita; Ningsih, Putri Ambarwati Listiya; Salsabila, Mutiara; Rafian, Ziddane; Rahman, Abdul (Ministrate: Jurnal Birokrasi dan Pemerintahan Daerah, 2025)
Climate change remains a pressing global issue, particularly in developing countries such as Indonesia, and is especially evident in major urban areas like the Special Capital Region of Jakarta (DKI Jakarta). In response, the Jakarta government has implemented electric vehicle (EV) policies as a strategy to reduce carbon emissions from the transportation sector. This study aims to analyze the effectiveness of these policies in curbing vehicular carbon emissions. Using a literature review approach, data were collected from various sources to evaluate existing regulations, identify challenges, and assess the potential of EVs in supporting a sustainable energy transition. The findings indicate that although there is regulatory support and government incentives, the adoption of electric vehicles continues to face significant obstacles, including high upfront costs, limited charging infrastructure, and inconsistencies in policy implementation. This study recommends strengthening coordination among government entities, the private sector, and the public to enhance accessibility and accelerate the adoption of environmentally friendly transportation solutions.